Closed-loop control of patient handling robots - Ziegler, Christian; Franke, Jörg (Studies in Computational Intelligence, 2013)
Patient handling robots are increasingly employed to enable a flexible positioning of the patient for diagnostic and therapeutic purposes. Due to the greatly differing robot loads because of varying patient weights especially serial kinematics are no longer able to keep up with the constantly increasing medical demands for positioning accuracy. In this chapter a low-cost measuring system for a permanent integration into the workspace of a patient handling robot is introduced which can measure the pose of a patient couch with high accuracy. This enables closed-loop control of the patient couch. In tests on a robot system an average positioning error of 0.12 mm was achieved for a diversity of medically relevant poses. © 2013 Springer-Verlag Berlin Heidelberg.
CRIS-Team Scopus Importer:2023-03-07

Dielectric elastomer actuators - On the way to new actuation-systems driving future assistive, compliant and safe robots and prostheses - Reitelshöfer, Sebastian; Landgraf, Maximilian; Yoo, In Seong; Hörber, Johannes; Ramer, Christina; Ziegler, Christian; Franke, Jörg (5th IEEE RAS/EMBS International Conference on Biomedical Robotics and Biomechatronics, 2014)
For almost 20 years, dielectric elastomer actuators (DEAs) have been the subject of intense research in material science. A large number of publications describe artificial muscles based on DEAs as a promising alternative for an energy efficient, lightweight and flexible actuation architecture. DEAs could improve and extend the capabilities of robotic and prosthetic devices in terms of their dynamical performance and their eligibility for energy autarkic operation. However, up to now DEAs are not available on a large scale with reproducible characteristics nor are they yet usable on a system integration level. In this paper we present recent findings of our ongoing five-year project to qualify DEAs as feasible artificial muscles for usage in compliant robot kinematics and soft prosthetic devices. The focus of this contribution lies on a new automated production process using Aerosol Jet Printing for stacked DEAs with very thin layers for reduced driving voltages and improved mechanical characteristics resulting from the additive manufacturing. Secondly, a new set of lightweight power electronics based on pulse width modulation (PWM) is presented which aims at the improvement of the overall specific power of DEA driven kinematic systems.
Keywords: compliant mechanisms; electroactive polymer actuators; prosthetics; robot kinematics; DEA driven kinematic systems; PWM; actuation systems; additive manufacturing; aerosol jet printing; artificial muscles; assistive robots; automated production process; compliant robot kinematics; dielectric elastomer actuators; lightweight power electronics; pulse width modulation; safe robots; soft prosthetic devices; Biomechatronics; Conferences; Robots

Highly Efficient Control System Enabling Robot Accuracy Improvement - Buschhaus, Arnd; Blank, Andreas; Ziegler, Christian; Franke, Jörg (5th CATS 2014 - CIRP Conference on Assembly Technologies and Systems, 2014)
The developed control system utilizes existing network technologies and uses data of sensor systems for continuous process monitoring to derive the robots actual state in course of its movement. In case of a high speed camera the image data is acquired by the control system via a first thread and subsequently the actual robot position is calculated based on this data. At the same time, for determining the robots target state, the system continuously requests the robots nominal position from the robot controller by utilizing a parallel second thread. The information describing the robots actual state is then compared with the sensor data for calculating offset values. These offset values are subsequently filtered and a correction value is calculated. In a third parallel thread new movement instructions are generated, considering the offset values as well as the robots target trajectory. Finally, for remote control of the robot, these movement instructions are transferred to the robot controller. (C) 2014 Elsevier B.V.
Keywords: Industrial Robot; Control System; Accuracy Improvement

My new colleague has artificial muscles: a DEA based approach for inherently compliant robotic systems - Yoo, In Seong; Landgraf, Maximilian; Ramer, Christina; Reitelshöfer, Sebastian; Ziegler, Christian; Franke, Jörg (Production Engineering, 2014)
Keywords: Artificial muscles; Compliant actuators; Dielectric elastomer actuators; Electroactive polymers; Human–robot collaboration; Safe robotic systems

Produktionsmanagement als effizientes Werkzeug zur Vernetzung von Forschungsprojekten - Ziegler, Christian; Stockinger, Andreas; Stoll, Tobias; Wittmann, Stefan; Weickmann, Johannes; Schmidt, Jürgen; Schuck, Marcus; Cojutti, Massimo; Al-Sheyyab, Ahmad (Zeitschrift für wirtschaftlichen Fabrikbetrieb, 2007)
LFT Import::2019-07-16 (1501)

Self-learning RRT* Algorithm for mobile robot motion planning in complex environments - Zhang, Xu; Lütteke, Felix; Ziegler, Christian; Franke, Jörg (Advances in Intelligent Systems and Computing, 2016)
RRT* is a practical and efficient incremental sampling-based motion planning algorithm. However, its searching ability is quite inefficient in some cases, due to relying on uniform random sampling like other RRT-based algorithms without taking the environment information and prior knowledge into account, which particularly leads to many sampling failures or generation of useless nodes in complex environments. In this paper, we propose an extension of RRT* based on a self-learning strategy and a hybrid-biased sampling scheme to improve the planning efficiency. By taking advantage of the prior knowledge accumulation and cost estimation, the searching tree has higher probability and success rate to extend in difficult areas. We also demonstrate the performance of our algorithm by building some simulation environments for our mobile robot and conclude with the results compared with RRT*.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Biased sampling; Mobile robot; Motion planning; RRT*

Sensor-guided jogging for visually impaired - Ramer, Christina; Ziegler, Christian; Reitelshöfer, Sebastian; Franke, Jörg (5th IEEE RAS/EMBS International Conference on Biomedical Robotics and Biomechatronics, 2014)
This paper introduces an approach for enabling visually impaired and blind people to practice jogging activities by 3D environment perception for course detection and collision avoidance, as well as feedback generation in an intuitive manner. Besides a system concept, first prototypic realizations, that confirm the general feasibility, are presented for this domain, which has not been addressed by research until now.
Keywords: handicapped aids; object detection; optical sensors; 3D environment perception; blind people; collision avoidance; course detection; feedback generation; optical sensors; sensor-guided jogging; visually impaired people; Belts; Cameras; Navigation; Sensors; Standards; Three-dimensional displays; Visualization

The LinKin System: A new robotic and universally applicable radiation therapy device - Ziegler, Christian; Franke, Jörg (2013 44th International Symposium on Robotics, ISR 2013, 2013)
This paper presents the LinKin System, a fundamentally new robotic radiation therapy device with six degrees of freedom. Because of its linear kinematics system design it has substantial advantages over common therapy devices. The highly flexible and universally applicable LinKin System opens a unique broad application range. Furthermore, due to its novel assistant functions it can be well-integrated into the clinic specific workflows. © 2013 IEEE.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Mechanisms and Kinematics; Medical Robots; Radiation Therapy